IMPROVING STUDENTS’ WRITING DESCRIPTIVE TEXT THROUGH THINK-PAIR-SHARE TECHNIQUE - Rika Febriyantika; Aseptiana Parmawati (PROJECT (Professional Journal of English Education), 2021)
Writing is troublesome to be  learned  and  taught for some students. One technique that can be used in teaching writing is TPS. The research was conducted in SMP Plus Nurulhidayah Pasundan. The researchers identify some problems, such as: 1) Does teaching writing using TPS improve the students’ writing creativity?, 2) How is the teaching and learning situation when TPS implemented in the writing class?. Classroom Action Research was used in this research. From the result of pre-test, we found that the result of students’ writing was under average and still far from what was expected. The finding was supported by the result of students’ writing scores. The average score of pre test was 47.1. After the implementation of TPS activities in every cycle, the students’ writing score were getting better. It can be seen from the result of students’ average score Cycle 1 was 51.8 and Cycle 2 was 71.09 It can be concluded that TPS can improve students’ writing creativity and TPS can improve writing classroom into a better situation. Keywords:  Think Pair Share, Writing Skill, CAR